The Entrepreneurial Role of Organized Labour in the British Columbia Motion Picture Industry - Murphy, David (Relations industrielles / Industrial Relations, 1997)
Research into an industrial sector reflecting principles of the emergent "network" model of production indicates that organized labour can play a positive role in post-Fordist Systems of industrial governance. Within the dynamic motion picture industry of British Columbia (B. C), organized labour was the key organizational factor in the birth and rapid expansion of the agglomeration ofsmall, specialized film production firms which has become a competitor for the coveted title of second largest film centre, after Los Angeles, in North America. In this process, B.C. film unions have become the dominant "actors " in forging collaborative relations between local production companies, between the sector and the state, and between the district and other film centers, so critical to the success of the network model.